Ectomycorrhizal fungi associated with Coccoloba uvifera (Polygonaceae) in coastal ecosystems of Eastern Cuba - Bullaín Galardis, Mijail (2024)
Introduction: Coccoloba uvifera, named also seagrape, establishes symbiotic relationships with many ectomycorrhizal fungi. However, in Cuba, these fungi have been little studied. Objective: To characterize the diversity of sporocarps and ectomycorrhizae of ectomycorrhizal fungi associated with C. uvifera in three coastal ecosystems of Eastern Cuba. Methods: Four samplings of sporocarps and ectomycorrhizae were carried out at three-week intervals during the rainy season, from June to September, in 2018 and 2019. Ectomycorrhizae were collected from three mature trees and 30 young individuals per tree. The samples were transferred to the Abiotic Stress Laboratory of the Center for Plant Biotechnology Studies of the University of Granma and the Laboratory of Plant Biology and Physiology of the University of French West Indies for processing and subsequent identification. Results: Five species of ectomycorrhizal fungi were identified from sporocarps collected under C. uvifera in the three sampling sites (Scleroderma bermudense, Russula sp., Cantharellus sp., Inocybe sp., and Amanita sp.). Using internal transcribed spacer sequencing, six taxa of ectomycorrhizal fungi were identified from ectomycorrhizas of mature trees and seedlings (S. bermudense, two Tuber spp., Tomentella sp., Inocybe sp., and Thelephora sp.). Only S. bermudense coincided (similarity 99-100 %) with sporocarps. S. bermudense was the most frequent ectomycorrhizal fungus in the ectomycorrhizas and sporocarps collected. Mature trees and C. uvifera seedlings shared between 75 and 100 % of the ectomycorrhizal fungal communities, being able to form potential common ectomycorrhizal networks. Conclusions: At the three collection sites, sporocarp weakly reflected the belowground ectomycorrhizal fungal community, ectomycorrhizal fungal diversity is quite limited, and S. bermudense was the only ectomycorrhizal fungus that overlapped in sporocarps and ectomycorrhizae.